Leslie Marmon Silko’s Ceremony: Hybridity in Identity Reconstruction - Qi, Zhou (Advances in Social Sciences Research Journal, 2020)
Ceremony, written by a Native American writer, Leslie Marmon Silko, tells a story of an old veteran Tayo’s journey to recover from after-war trauma and to reconstruct his identity. Due to the inherent hybridity existed in many aspects, including mix-blood identity, occupied land and assimilated culture, hybridity leads to Tayo’s identity loss. However, because of its uniqueness and strength in combining heterogeneous cultures, hybridity has also contributed greatly to Tayo’s identity reconstruction. Focusing on the vital role of hybridity played in reconstructing Tayo’s identity, this essay analyzes how hybridity functions throughout the whole process from identity loss to identity quest, and finally to identity reconstruction. In this novel, the retrieval of the spotted cattle, the transformed ceremony developed from the traditional ones, as well as the changed attitude towards the existence of hybridity have all represented a new perspective of viewing hybridity. With the interwoven of modern culture, it requires us to realize that inheriting and developing Indian traditional culture should not be complacent or conservative. Instead, we should take great advantage of hybridity by absorbing beneficial factors from different cultures into traditional ones, thus enabling it to better develop in the constant changing world.